2009
DOI: 10.3163/1536-5050.97.2.009
|View full text |Cite
|
Sign up to set email alerts
|

Disappearing act: decay of uniform resource locators in health care management journals

Abstract: URL decay is a serious problem in health care management journals. In addition to using website archiving tools like WebCite, publishers should require authors to both keep copies of Internet-based information they used and deposit copies of data with the publishers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 30 publications
(48 reference statements)
3
49
1
1
Order By: Relevance
“…5,6,7 In 2015, upon the twenty-year benchmark of the original data collection, Oguz and Koehler reported in JASIS that only 2 of the original links remained active. 8 A number of foundational studies, including Casserly and Bird, 9 Spinellis, 10 Sellitto, 11 Falagas, Karveli, and Tritsaroli, 12 and Wagner et al 13 have reported on linkrot occurring in professional literature. Sanderson, Phillips, and Van de Sompel provide a table of 17 well-known linkrot studies, comparing overall benchmarks, and supplying a succinct summary of the scope of each study.…”
Section: Smoking Gunsmentioning
confidence: 99%
“…5,6,7 In 2015, upon the twenty-year benchmark of the original data collection, Oguz and Koehler reported in JASIS that only 2 of the original links remained active. 8 A number of foundational studies, including Casserly and Bird, 9 Spinellis, 10 Sellitto, 11 Falagas, Karveli, and Tritsaroli, 12 and Wagner et al 13 have reported on linkrot occurring in professional literature. Sanderson, Phillips, and Van de Sompel provide a table of 17 well-known linkrot studies, comparing overall benchmarks, and supplying a succinct summary of the scope of each study.…”
Section: Smoking Gunsmentioning
confidence: 99%
“…Most authors citing Internet source material in academic publications assume that the material they cite can be retrieved. Over the past decades, Internet reference accessibility loss has been explored primarily in cross sectional studies (Hester et al 2004; Thorp and Brown 2007;Crichlow et al 2004;Habibzadeh 2013; Thorp and Schriger 2011;Wagner et al 2009;Wu 2009). These studies all raised concerns about the accessibility loss of Internet references.…”
Section: Introductionmentioning
confidence: 99%
“…Study revealed a fact that search engines in combination with Internet Archive retrieved 98% of the retrievable web references. In the same year, Wagner et al (2009) examined a total of 2011 URLs were found cited in five medical science journals, of which 49.3 percent were found missing. They tried to find the missing online content and used Internet Archive and Google search engine.…”
Section: Recovery Of Vanished Urlsmentioning
confidence: 99%